الأخطاء الترجمية وأثرها في ثقافة المتلقي ولغته: Errors Of Translation And Their Effect On The Receptor's Culture And Language - نعماني , حفصة; عيساوي , عبد الرحمن (Maalim, 2026)
The translator’s aim is to make understand the receptor what he/she cannot understand in a foreign language. A bad translation is the one which does not satisfy the listener / reader either linguistically or culturally. However, some translations may be misleading and may include some errors of which the receptor is unaware. We attempt in this paper to study some errors of translation that may affect the receptor’s culture or language so that learner-translators must avoid them as possible as they can.